Budget impact of capmatinib for adults with metastatic non-small cell lung cancer harboring a MET exon 14 skipping mutation in the United States. (1st January 2021) - Cai, Beilei; Zhou, Zheng-Yi; Xue, Weiguang; Hazra, Nisha C.; Singh, Mukesh; Mishra, Dinesh; Brixner, Diana; Oderda, Gary; Biskupiak, Joseph
Abstract: Aims: To estimate the budget impact of adding capmatinib, the first FDA approved MET inhibitor, to a US commercial or Medicare health plan for patients with metastatic non-small cell lung cancer (mNSCLC) whose tumors have a mutation that leads to MET exon 14 ( MET ex14) skipping. Methods: Target population size was estimated using published epidemiology data. Clinical data were obtained from the GEOMETRY mono-1 capmatinib trial and published trials. Treatments in the market mix included crizotinib, pembrolizumab, ramucirumab, and chemotherapy. Uptake of capmatinib and testing rates were based on market research. All costs (drug acquisition and administration, pre-progression, progression, terminal care, adverse event, and testing) were estimated based on public sources (2020 USD). Results: The number of patients eligible for capmatinib in the first three years was estimated to be 2–3 in a hypothetical 1 million member commercial plan and 34–44 in a hypothetical 1 million member Medicare plan each year. The estimated total budget impact ranged from $9, 695 to $67, 725 for a commercial plan and $141, 350 to $985, 695 for Medicare. With capmatinib included, a marginal per member per month budget impact was estimated (commercial: $0.0008 to $0.0056; Medicare: $0.0118 to $0.0821). Capmatinib inclusion resulted in lower medical costs (commercial: –$0.0003 to –$0.0007; Medicare: –$0.0037 to –$0.0106), partially offsetting increased drug costs ($0.0011 to $0.0064; $0.0154 to $0.0928, respectively), and were primarily driven by reductions in progression and terminal care costs (–$0.0003 to –$0.0009; –$0.0037 to –$0.0125, respectively). The results were most sensitive to capmatinib market share, capmatinib price, and treatment duration. Limitations: Certain assumptions were applied to the model to account for inputs with limited evidence. Conclusions: The estimated budget impact of including capmatinib for mNSCLC with a MET ex14 skipping mutation is minimal, and the increased drug costs were partially offset by savings in AEs, and progression-related and terminal care costs.